2013
DOI: 10.1155/2013/475964
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplantation from Elderly Living Donors

Abstract: Acceptance of elderly living kidney donors remains controversial due to the higher incidence of comorbidity and greater risk of postoperative complications. This is a review of publications in the English language between 2000 and 2013 about renal transplantation from elderly living donors to determine trends and effects of donation, and the outcomes of such transplantation. The last decade witnessed a 50% increase in living kidney donor transplants, with a disproportionate increase in donors >60 years. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…Although extended criteria donors are getting more and more accepted as an alternative for optimal donors, the outcome after transplantation of an ECD kidney is worse, with higher risks of DGF, acute rejection and graft failure [25] . Since age is a factor that cannot be influenced, reducing the consequences of ischemia is all the more warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Although extended criteria donors are getting more and more accepted as an alternative for optimal donors, the outcome after transplantation of an ECD kidney is worse, with higher risks of DGF, acute rejection and graft failure [25] . Since age is a factor that cannot be influenced, reducing the consequences of ischemia is all the more warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Donors to the AGD group were significantly older (42.54 ± 11.45 years); and although they were found in a state of perfect health, age could be an independent factor in the appearance of AGD. In this regard, it has been previously reported that the acceptable age of live kidney donors continues to be controversial due to the higher incidence of comorbidities and greater risk of postoperative complications [21, 22]. …”
Section: Discussionmentioning
confidence: 99%
“…Transplantation of liver from the individuals above the age of 55 years [14][15][16][17] or renal transplants from individuals more than 65 years have shown a higher failure rate than donations from younger individuals. 18,19,20 It has been reported that with increasing age, the number of organs discarded increases. 21 Harvesting good quality organs from cadavers under the prescribed manner according to the law of the country helps to save valuable human lives.…”
Section: Donations Upon Deathmentioning
confidence: 99%